Double Triangular Cartilage Excision in Otoplasty Revisited - Gualdi, Alessandro; Cambiaso-Daniel, Janos; Negrini, Filippo Contessi; Giordano, Salvatore (Facial Plastic Surgery, 2024)
Background Prominent ears negatively impact the psychological and social health of individuals. Despite the availability of different surgical correction methods for this congenital condition, many of these techniques might result in significant risks of complications and the condition often reappears. Herein, we present log-term outcomes of our suture-free method that employs various strategies to reduce these risks and prevent recurrences.Methods We analyzed the results of patients who had a bilateral double triangular cartilage excision otoplasty as an outpatient procedure. This previously described technique is designed to correct prominent ears by precisely removing sections of cartilage to reshape the ear mechanically without the need for sutures through the cartilage. We documented any complications after surgery and gathered feedback from patients over an extended follow-up period.Results A total of 146 patients (292 ears) met the inclusion criteria. The mean age was 23.2 ± 5.3 years. The mean follow-up period was 22 months. Complications were as follows: 3 ears (1.02%) showed superficial skin tissue necrosis at the front of the ear and 17 ears (5.8%) needed further surgery due to unsatisfactory ear rotation. Additionally, 2.73% experienced wound dehiscence, 0.68% had hematomas, 1.02% had external ear infections that were treated with local and systemic antibiotics, 4.1% developed hypertrophic scars, and 8.2% experienced temporary paresthesias. Patients reported being satisfied with the final outcomes at follow-up.Conclusion Double triangular cartilage excision otoplasty is a safe procedure with few complications, low recurrence rates, and good patients' satisfaction at long-term follow-up. This sutureless technique should be included as an alternative to the existing surgical techniques and added to the skill set of surgeons.Level of Evidence IV.
Keywords: otoplasty; prominent ears; conchal hypertrophy; antihelix; complications; patient-reported outcomes